To study the effect of oxygen carrying capacity on expressed changes of erythrocyte membrane protein in different storage times. Issue 6 (25th June 2020) - Wang, Huan; Wei, Han-Wei; Shen, Hua-Chun; Li, Zhen-Zhou; Cheng, Yong; Duan, Li-Shuang; Yin, Lei; Yu, Jun; Guo, Jian-Rong
Abstract: Erythrocyte membrane is crucial to maintain the stability of erythrocyte structure. The membrane protein on the surface of erythrocyte membrane enables erythrocyte to have plasticity and pass through the microcirculation without being blocked or destroyed. Decreased deformability of erythrocyte membrane protein will lead to a series of pathological and physiological changes such as tissue and organ ischemia and hypoxia. Therefore, this research collected 30 cases of healthy blood donors, and explored erythrocyte stored at different times relating indicators including effective oxygen uptake (Q), P50, 2, 3-DPG, Na + -k + -ATP. Erythrocyte morphology was observed by electron microscopy. Western blot and immunofluorescence assay were used to detect membrane protein EPB41, S1P, GLTP, SPPL2A expression changes of erythrocyte. To explore the effective carry oxygen capacity of erythrocyte at different storage time resulting in the expression change of erythrocyte surface membrane protein.